The Effect of Multi-Stage Discussion with Google Classroom and WhatsApp in Learning Physics on Problem Solving Ability - Sulistia Ningsih; Wayan Suana; Feriansyah Sesunan (Universitas Lambung Mangkurat, 2021)
This research describes the effect of applying multi-stage discussion with Google Classroom and WhatsApp in learning physics on students' problem-solving abilities. Google Classroom media was used for large group discussions and WhatsApp for small group discussions. The design in this research used a pre-experimental design in the form of a one-group pretest-posttest design with apurposive sampling technique for three meetings on Newton’s Law of Motion with experimented classes with a total sample of 60 students. Data were analyzed using paired sample t-test.The results showed a difference in the average students’ problem-solving abilities before and after treatment with a Sig. (2-tailed) value of 0.000. After implementinglearning multi-stage discussion with Google Classroom and WhatsApp, students' problem-solving ability in the experimental class increased from the very low to moderate category with an average N-gain of 0.66. The highest increase occurred in theindicators of physics approach and mathematical procedure with an average N-gain of 0.71 and the lowest increase in thehelpful indicator description with an average of 0.63. This increase shows that the application oflearning multi-stage discussion with Google Classroom and WhatsApp on Newton's Laws of Motion has a moderate effect on students' problem-solving abilities.